Shape optimisation and performance analysis of flapping wings - Ghommem, M.; Collier, N.; Niemi, A.; Calo, Victor (2012)
In this paper, we consider the shape optimization of flapping wings in forward flight. This analysis is performed by combining a gradient-based optimiser with the unsteady vortex lattice method. The objective is to identify a set of optimised shapes that maximise the propulsive efficiency under lift, thrust, and area constraints. The geometry of the wings is modelled using B-splines. The flow simulations using the optimal wing shapes indicate that changes in the shape have significant effects on averaged quantities. The optimal shape configuration substantially increases the time averaged thrust while, at the same time, it acquires a larger input of aerodynamic power. Increasing the number of variables (i.e., providing the wing shape with a greater degree of spatial freedom) enables increasingly superior designs. This study should provide better guidance for shape design of engineered flying systems. © Civil-Comp Press, 2012.